Perbandingan Efektivitas Metode Natif Dan Sedimentasi Dalam Deteksi Telur Cacing Ascaris Lumbricoides Di TPS Kecamatan Gebog - Ririn Handayani; Shinta Dwi Kurnia (Poltekkes Kemenkes Semarang, 2026)
The World Health Organization (WHO) reports that more than 1.5 billion people are infected with soil-transmitted helminths (STH). Ascaris lumbricoides infection remains a health problem in areas with poor sanitation, such as waste disposal sites (TPS). Detection of helminth eggs in fecal samples is important to determine the level of environmental contamination and the effectiveness of prevention. The aim of this study is to improve the effectiveness of parasitological examinations in laboratories through the use of more specific methods. This study is motivated by the still high risk of helminth infections, especially Ascaris lumbricoides, in environments with poor sanitation such as temporary disposal sites (TPS) and to determine the effectiveness of native and sedimentation methods in detecting Ascaris lumbricoides eggs in fecal samples of TPS officers in Gebog District. This study uses a laboratory experimental method with a comparative approach. Fecal samples were taken from potentially contaminated TPS officers, then examined using the Native method (direct examination) and Sedimentation (with 0.9% NaCl solution). Parameters considered included the number and shape of Ascaris lumbricoides eggs found, as well as the efficiency of each method. The data analysis used McNemar statistics. The results showed no statistically significant difference between the native and sedimentation methods. This means that both methods have nearly equal ability to detect Ascaris lumbricoides eggs in the fecal samples of polling station officers in Gebog District.The parameters observed included the number and shape of Ascaris lumbricoides worm eggs found, as well as the efficiency of each method. Data analysis used Wilcoxon statistics. The results of this study The Wilcoxon test results show that of the 27 fecal samples, N = 0 (Sedimentation < Native) was found, this indicates that no sample produced better results from both methods, either the native or sedimentation method. In the comparison category N = 1 (Sedimentation > Native) this shows that there is 1 sample that was detected by the sedimentation method better than the native method. While the results of the Sedimentation = Native (Ties) test mean that some samples 26 out of 27 showed the same results from both methods. A p value of 0.317 (p > 0.5) was obtained. These results indicate that there is no statistically significant difference between the native method and the sedimentation method. This means that both methods have almost the same ability to detect Ascaris lumbricoides eggs in the feces samples of polling station officers in Gebog District.